دور أدوات الدفع المالية في تمويل تجارة العراق الخارجية للمدة (2003-2020) دراسة تحليلية: The Role of Financial Payment Tools in Financing Iraq’s Foreign Trade for The Period (2003-2020) - Al-Yasiri , Ahmed (The Gulf Economist, 2023)
The expansion of foreign trade is linked to the nature of the tools used in it. The more developed and advanced these tools are, the more they lead to an expansion of the volume of foreign trade, reducing the risks related to international trade, and becoming more secure between the exporter and the importer. The Iraqi economy faces the problem of providing financial resources represented in foreign currencies, due to the diversity of its import needs that require large financing of foreign currencies to cover the value of those imports, on the other hand, the only source for obtaining these currencies is oil exports, which are always exposed to the problems of low oil prices and low quantities of demand Because of the economic crises that the global economy in general and the Iraqi economy is exposed to in particular, therefore, the process of financing foreign trade and the possibility of using internationally known financial tools in implementing the financing process is one of the most important problems facing the Iraqi economy due to its great dependence on the foreign trade sector. The research seeks to know how Iraq's foreign trade is financed, whether in the government sector trade or the private sector. Access to the most important tool in financing foreign trade in Iraq and to identify the new tools used in this field as well.